Biomass prediction models for Colophospermum Mopane (Mopane) in Botswana - Mutakela, Patrick Silishebo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MFor (Forest and Wood Science))--University of Stellenbosch, 2009.